1998
DOI: 10.2105/ajph.88.1.108
|View full text |Cite
|
Sign up to set email alerts
|

HIV seroprevalence among street-recruited injection drug and crack cocaine users in 16 US municipalities.

Abstract: OBJECTIVES: This study deter- mined human immunodeficiency virus (HIV) seroprevalence and factors associated with HIV infection among street-recruited injection drug users and crack cocaine smokers. METHODS: An analysis was performed on HIV serologies and risk behaviors of 6402 injection drug users and 3383 crack smokers in 16 US municipalities in 1992 and 1993. RESULTS: HIV seroprevalence was 12.7% among injection drug users and 7.5% among crack smokers. Most high-seroprevalence municipalities (>25%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(73 citation statements)
references
References 42 publications
(3 reference statements)
4
66
3
Order By: Relevance
“…Crack cocaine is the drug of choice in this study, as 98% of the participants used this drug, with very few using other drugs, such as methamphetamines. Several studies have shown that crack cocaine users engage in more unprotected sexual acts, trade sex for money or drugs and have more sexually transmitted diseases, all factors contributing to greater risk for HIV infection [17,21,[23][24][25][26]. One third of the study participants had a history of injection drug use, but no associations were identified between IDU and HIV infection in males or females in this study, a conflicting finding from other studies [27][28][29][30][31].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Crack cocaine is the drug of choice in this study, as 98% of the participants used this drug, with very few using other drugs, such as methamphetamines. Several studies have shown that crack cocaine users engage in more unprotected sexual acts, trade sex for money or drugs and have more sexually transmitted diseases, all factors contributing to greater risk for HIV infection [17,21,[23][24][25][26]. One third of the study participants had a history of injection drug use, but no associations were identified between IDU and HIV infection in males or females in this study, a conflicting finding from other studies [27][28][29][30][31].…”
Section: Discussioncontrasting
confidence: 85%
“…The median age of the study participants in this study is 43, and documented to be participating in risky drug and sexual behaviors, plus vulnerable to infection, therefore, increasing age is an understandable risk. Sexual behavior in noninjecting drug users may be influenced by stimulant drug activity, especially crack cocaine [17,21,[23][24][25][26], influencing the drug user to participate in risky sexual behaviors, resulting in increased risk for HIV, hepatitis B, and STDs. From our previous studies and others, there was no significant association found between HCV infection and sexual risk behaviors [4,34].…”
Section: Discussionmentioning
confidence: 99%
“…2 Study sites included San Jose and Los Angeles, California; Baltimore, Maryland; New York City's Lower East Side and Harlem; New Haven, Connecticut; and Chicago, Illinois. Eligible participants were at least 18 years old and had injected illicit drugs at least once in the past year.…”
Section: Study Populationmentioning
confidence: 99%
“…4 HIV Incidence Varies Geographically and Declined by the Late 1990s In the 1990s, national studies funded by CDC and the National Institute on Drug Abuse (NIDA) estimated the overall HIV prevalence among urban IDUs to be from 12.7 to 14.6%, with consistently higher rates for IDUs in east coast cities than in west coast cities. 1,5,6 Studies in east coast cities showed HIV incidence in the range of 2.7 to 10.7 per 100 person-years, while HIV incidence among IDUs in west coast cities typically showed an HIV incidence of 0.3 per 100 person-years or less. [7][8][9][10] The overall HIV incidence among IDUs peaked in the early to mid-1980s and then declined by the late 1990s.…”
Section: What Are the Epidemiologic Trends In Hiv Among Idus In The Umentioning
confidence: 99%